Reassessing Reification: Ethnicity amidst “Failed” Governmentality in Burma and India - Prasse-Freeman, Elliott (Comparative studies in society and history, 2023)
In part because a single colonial project eventually formally incorporated Burma as an appendage to British colonial rule of India, Burma scholars persistently draw on historiography and anthropology of India to assert that ethnic categories in Burma were “reified” and hierarchized by colonial governmentality and ensuing postcolonial statecraft. This article disputes such assumed equivalences, re-theorizing “reification” through the concept of governmentality to distinguish modes of regulation and the kinds of social responses incited, suggesting that India and Burma stand as respective exemplars of distinct governmental forms. Specifically, scholarship represents Indian population groups (of caste, tribe, ethnicity, etc. permutations) as being reified by dense and reinforcing applications of knowledge/power. Even when these various and interlinking regulatory apparatuses “fail” to accurately describe social reality, they interpellate a response from subject populations, a process that operates to dialectically reinforce the categories. Conversely, similar governmental apparatuses desultorily implemented in Burma have operated differently. While they have succeeded in making South Asian and Muslim subjects into Burma’s self-perceived constitutive outside, governmentality has “doubly failed” on its taingyintha (indigenous) subjects. Poor knowledge of these Burmese peoples has foreclosed intensive projects of knowledge production, leading to “misinterpellation,” a form of metapragmatic awareness in which subjects recognize that discourses misdescribe them, and then strategically maneuver with(in) those labels. Ethnic emblems become hollow integuments navigable with comparative ease, as individuals modify their particular bodily and dispositional indices. The article concludes by encouraging comparative postcolonial governmentality studies that would delineate particularities in a concept (governmentality) that often remains unnuanced.